2003
DOI: 10.1016/s0022-5223(02)73229-7
|View full text |Cite
|
Sign up to set email alerts
|

Blocking the development of postischemic cardiomyopathy with viral gene transfer of the apoptosis repressor with caspase recruitment domain

Abstract: Gene transfer of apoptosis repressor with caspase recruitment domain preserves left ventricular function after ischemia. The benefit at 6 weeks is postulated to result from an apoptosis repressor with caspase recruitment domain-mediated reduction in apoptosis and ventricular remodeling. Adenovirus-apoptosis repressor with caspase recruitment domain administration offers a potential strategy after myocardial ischemia to protect the heart from late postischemic cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 23 publications
(25 reference statements)
0
33
1
Order By: Relevance
“…The present results confirmed this report and demonstrated that a moderate hypercholesterolemia (2% cholesterol diet for 8 weeks) also increased myocardial apoptosis. Several studies stated that inhibition of apoptosis by a variety of pharmacological and genetic approaches results in smaller infarction (Brocheriou et al, 2000;Mocanu et al, 2001) and improved cardiac function (Abbate et al, 2002;Chatterjee et al, 2003). Taurine, is known as to protect various disorders and has been demonstrated to have beneficial effects in nephropathy, cardiomyopathy and neuropathy, (Szymanski and Winiarska, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The present results confirmed this report and demonstrated that a moderate hypercholesterolemia (2% cholesterol diet for 8 weeks) also increased myocardial apoptosis. Several studies stated that inhibition of apoptosis by a variety of pharmacological and genetic approaches results in smaller infarction (Brocheriou et al, 2000;Mocanu et al, 2001) and improved cardiac function (Abbate et al, 2002;Chatterjee et al, 2003). Taurine, is known as to protect various disorders and has been demonstrated to have beneficial effects in nephropathy, cardiomyopathy and neuropathy, (Szymanski and Winiarska, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the intrinsic pathway involves interactions between ARC and the C-terminal regulatory domain of Bax (Bcl-2-associated X protein) that prevent the conformational activation of Bax and its translocation to the mitochondria in response to apoptotic stimuli (12,13). Overexpression of ARC blocks cell death in response to activators of both extrinsic and intrinsic pathways (9,(12)(13)(14)(15)(16)(17). Conversely, knock down of endogenous ARC promotes activation of both pathways (12).…”
mentioning
confidence: 99%
“…This is supported by the observation that exogenous ARC reduces infarct size after ischemia/reperfusion (I/R) injury of isolated perfused rat hearts and blocks the development of postischemic cardiomyopathy. 13,14 Despite several overexpression studies on ARC, little is known about its endogenous function. However, this is of particular significance because exposure of cardiomyocytes to ischemia, hypoxia, or oxidative stress leads to a rapid downregulation of ARC protein levels with subsequent cell death in vitro, suggesting that decreasing ARC levels may function as a critical switch of cardiomyocyte survival.…”
mentioning
confidence: 99%